Principles of Context Aparihaniyadhamma and Political Behavior - Nammasid, Phanuwat (Journal of Sustainable Social Development, 2024)
This academic article sees that the concept of democracy assumes that the people are the owners of sovereignty. Under the principle of separating and checking the use of power There is an organization that exercises legislative power. Organizations exercising executive power and organizations exercising judicial power It is the exercise of sovereignty on behalf of the people. Because of the political role of the people as owners of sovereignty, it is the heart of democracy. Results of the study: The 7 Aparihaniyadhamma principles are principles of shared responsibility that will help prevent deterioration. Leads to prosperity in the following ways: 1. Regularly meet together regularly. 2. Meet together in unison. 3. Do not be arbitrary and desire convenience. 4. Anyone who is an adult has long experience. 5. Honor and protect women. 6. Respect Pay homage to the sacred pagoda. 7. Provide righteous care, nourishment, and protection to the monks who have good morals. Political behavior means the expression of politics in actions or feelings and political attitudes. As well as political participation in various forms, whether it results in development, cooperation or conflict. Political behavior comes in many forms, such as voting in elections. Compliance with the law As for the factors related to political behavior above. Relevant factors can be divided into 2 parts: external factors or environmental factors in various contexts such as social, economic, political, cultural contexts, etc., and the second factor is factors that arise from the individual. That affects stimuli, perceptions, attitudes, beliefs, etc. These factors affect the decision for people to come out and exercise their right to vote. The knowledge of the 7 principles of Aparihaniyadhamma is a principle of shared responsibility that will help prevent deterioration. Leads to prosperity for individuals and organizations as follows: Regularly meet together. Meet together in unison. 3. Do not be arbitrary and desire convenience. Anyone who is an adult has a long experience. Honor and protect women Pay homage to the sacred pagoda and provide righteous protection that facilitates the expression of people’s political behavior, namely in terms of political behavior Political participation Political knowledge and following political news Briefly summarized, the 7 Aparihaniyadhamma principles can influence people’s political behavior to express themselves in an appropriate political way and prevent political violence.